Silk Sericin Hydrolysate is a Potential Candidate as a Serum-Substitute in the Culture of Chinese Hamster Ovary and Henrietta Lacks Cells - Zhang, Meng (J Insect Sci, 2019)
The silk sericin hydrolysate (SSH) from the waste of silk processing as a substitute of fetal bovine serum (FBS) was used for the culture of Chinese hamster ovary (CHO) cells and Henrietta Lacks (Hela) strain of human cervical cancer cells. The survival ratio of these cells cultured in SSH media were similar to or higher than those in FBS media. Especially after the serum was replaced by low concentration of SSH at 15.0 μg/ml for 5 d, the proliferation of both cells was also similar to or higher than that of FBS group; the percentages of CHO and Hela cells in S-phase were 28.9 and 28.0%, respectively. The former is nearly two times that of FBS group, the latter is also higher than the control group. Reverse transcription-polymerase chain reaction (RT-PCR) revealed that among the differentially expressed genes, the relative expression of CXCL12 gene of CHO cells in SSH group increased, was three times that of serum group, and the relative expression of LCN2 gene of Hela cells increased 2.8 times, indicating that these related genes were activated to promote cell growth and proliferation. These results fully illustrated the hydrolysated sericin has a potential use as serum substitutes in cell culture.